2020
DOI: 10.3389/fvets.2020.00505
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Cannabidiol, Cannabidiolic Acid, Δ9-Tetrahydrocannabinol, Tetrahydrocannabinolic Acid and Related Metabolites in Canine Serum After Dosing With Three Oral Forms of Hemp Extract

Abstract: Cannabidiol (CBD)-rich hemp extract use is increasing in veterinary medicine with little examination of serum cannabinoids. Many products contain small amounts of Δ9-tetrahydrocannabinol (THC), and precursor carboxylic acid forms of CBD and THC known as cannabidiolic acid (CBDA) and tetrahydrocannabinolic acid (THCA). Examination of the pharmacokinetics of CBD, CBDA, THC, and THCA on three oral forms of CBD-rich hemp extract that contained near equal amounts of CBD and CBDA, and minor amounts (<0.3% by weight)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
104
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(137 citation statements)
references
References 37 publications
10
104
7
Order By: Relevance
“…In humans, elimination is rapid with reported elimination half‐lives of 1.09 and 1.97 hr following oral administration of 10 and 20 mg, respectively 29,30 and 2.95 and 3.21 hr following oral ingestion of 10‐mg lipid capsules 31,32 . In dogs, while the elimination half‐life is longer (3.8–4.4 hr) 28 ; than that reported for humans, it is shorter than for horses. Elimination appears to be dose independent over the range of doses administered in the current study as evidenced by a similar elimination half‐life at each dose.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In humans, elimination is rapid with reported elimination half‐lives of 1.09 and 1.97 hr following oral administration of 10 and 20 mg, respectively 29,30 and 2.95 and 3.21 hr following oral ingestion of 10‐mg lipid capsules 31,32 . In dogs, while the elimination half‐life is longer (3.8–4.4 hr) 28 ; than that reported for humans, it is shorter than for horses. Elimination appears to be dose independent over the range of doses administered in the current study as evidenced by a similar elimination half‐life at each dose.…”
Section: Discussionmentioning
confidence: 93%
“…This is in agreement with what is reported in the current study primary metabolites found in blood and urine in horses are 7‐COOH CBD and 7‐OH CBD. Although detectable, Wakshlag and colleagues 28 reported that 7‐OH CBD concentrations were below the LOQ in blood. Similarly, in the current study, concentrations of this metabolite were low in blood at all times post drug administration with the carboxylated metabolite (7‐COOH CBD) predominating.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency for dogs in the HIGH CBD treatment to be less active than CON dogs in the p.m. may indicate that CBD exerted some sedative or calming effect on the dogs. However, this potential sedative effect was expected to be observed in the a.m., as previous pharmacokinetic reports have shown a half-life for CBD of 1–4 h ( 35 , 51 , 52 , 57 ). As this effect was not observed during the a.m. sessions, exercise periods, or overall daily activity, these collective results do not support a sedative or calming effect of CBD in dogs.…”
Section: Discussionmentioning
confidence: 93%
“…Many have been puzzled by the high bioavailability of CBDA in humans following the oral ingestion of CBD-dominant cannabis-derived nutraceutical oils 5 , 55 57 . Our results suggest that the oral administration of such cannabis extracts provides a natural vehicle to enhance plasma CBDA concentrations due to cannabinoid-cannabinoid interactions at the drug efflux transporter BCRP.…”
Section: Discussionmentioning
confidence: 99%